Integrative Review of Indonesian Phytocosmetics: Resveratrol, Collagen, and Pachyrhizus erosus for Anti-Aging and Skin-Brightening in Multipurpose Serum - Sofiani Lathifah; Kintoko Kintoko; Pradanty Anaperta Gulies Sentana (Jurnal FARMASIMED (JFM), 2026)
Background: The demand for natural-based cosmetic products has increased substantially, driven by consumer awareness of safety, efficacy, and sustainability, with facial serums being preferred for anti-aging and skin-brightening applications. Objective: This review aimed to synthesise scientific evidence on the potential of resveratrol, marine collagen, and jicama (Pachyrhizus erosus) extract as key actives in multipurpose facial serum formulations with antioxidant, anti-ageing, and skin-brightening claims. Methods: A narrative review was conducted using original research articles published between 2015 and 2025 retrieved from PubMed and Crossref databases, focusing on quantitative outcomes including antioxidant and antityrosinase IC₅₀ values, changes in skin elasticity and hydration, transepidermal water loss (TEWL), and molecular biomarkers of skin ageing. Results: Of 1,393 identified records, 20 studies met the inclusion criteria (resveratrol n=6; collagen n=8; P. erosus n=6). Resveratrol shows strong antioxidant and anti-inflammatory activities that mitigate UV-induced photoaging; marine collagen, particularly hydrolysates, improves skin hydration and elasticity; and jicama extract provides antioxidant activity, including phenolic- and flavonoid-rich compounds, with tyrosinase inhibitory effects. Conclusion: Integrating these three actives may offer synergistic multi-target benefits; however, further formulation studies and clinical evaluations are required to confirm stability, compatibility, and combined efficacy within a single serum product.